Brand perceptions based on visuals and message appeals : communicating a Finnish luxury brand on Instagram - Lehtonen, Aino (2020)
Luxury brands’ social media communication has been an important topic in the field of marketing research. While the topic is important for academics, it is also crucial for the businesses to understand what kind of content they should publish in order to project a brand image of luxury. However, marketing research has not yet shown how the Finnish consumer views the Finnish luxury brands on social media platforms. The Finnish people hold a rather peculiar, even a slightly negative attitude toward luxury, and therefore, marketing research ought to be conducted in this context. The starting point of this study was rather practical: what kind of social media content a Finnish luxury brand should create in order to be perceived as luxurious but yet fitting to the social media world? Thus, the purpose of this study was to discover how the Finnish consumer perceives the brands behind social media posts based on mere visual and textual content. To start the exploration to the topic, it was important to identify what kind of content is currently posted by Finnish luxury brands. After this, a set of interviews were conducted to answer the main research objective: to discover the brand perceptions a Finnish consumer receives from certain type of visual and message appeals displayed in a social media post. The study results confirmed some previous research findings: Finnish consumers connect simple, low visual complexity images with classical luxury brands, however the complexity of the visual did not matter for the luxuriousness of brand. For the content itself, resonance appeal which describes what is occurring in the visual, was discovered to be an important component in Instagram content, linking it to easy information processing. Also, the Finnish consumer perceives international luxury brands more luxurious than Finnish ones and separates these two types of luxury brands, the international and Finnish, to two completely different categories, which produce different kind of Instagram content.